Determination of citrat ions in drugs on molecular luminescence of rutine in complex with yttrium (III) - S. V. Beltyukova; O. V. Malynka; O. O. Livencova (The State Expert Center of the Ministry of Health of Ukraine, 2019)
The development of methods for qualitative and quantitative analysis of drugs can guarantee their identity and quality. Drugs used in the form of salts of organic bases are often determined by the anionic part of these salts. Citrate ions are a part of many drugs in the form of citric acid, salts of alkaline and alkaline earth metals. The purpose of this study was to develop a method for the luminescent determination of citrate ions in dosage forms using a complex of yttrium (III) with rutine (Rut) as a luminescent probe. It has been experimentally established that citrate ions increase the luminescence intensity of the Y(III)-Rut complex. The spectral and luminescence characteristics of the complex was studied. The luminescence spectrum of the Y(III)-Rut complex has a maximum at λlum = 570 nm. The luminescence intensity of the Y(III)-Rut complex increases and the luminescence peak shifts to the short-wave region of the spectrum (λlum = 522 nm) in the presence of sodium citrate. The maximum effect is observed at a pH of 6.5-7.5. The dependencies of the luminescence intensity on the concentration of Y(III) and Rut for the Y(III)-Rut-Cit complex at the constant concentration of citrate ions (1·10-3 mol/l) were studied. It was established that the maximum luminescence intensity was observed at concentrations of Y(III) - 2·10-3 mol/l and Rut - 5·10-4 mol/l. The linear region of the dependence of the luminescence intensity of the complex on the concentrations of Y(III) and Rut is observed in the range of yttrium concentrations 0.3-2.0·10-3 mol/l and rutine 0.5-5.0·10-4 mol/l. The method of luminescent determination of citrate ions in dosage forms has been developed. The method is based on the use of rutine molecular luminescence in the multi-ligand complex Y(III)-Rut-Cit. The method of determination of citrate ions in dosage forms differs favorably from the existing absence of toxic reagents, expensive equipment, short-term analysis time, allows rapid screening of samples of drugs.